2004
DOI: 10.1290/1543-706x(2004)40<35:cohmcl>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human Melanoma Cell Lines According to Their Migratory Properties in Vitro

Abstract: The migratory responses of four human melanoma cell lines (A-2058, DEMEL, HTB-63, and HTB-72), using chemotaxis (CTX) and haptotaxis (HPTX) assays, were studied. The attractants were three extracellular matrix components (EMCs), fibronectin, laminin, and collagen type IV. The conditioned media (CM) of each cell line were used to study autocrine and paracrine responses. A screening and sensitive CTX assay was performed, using pertussis toxin (PTX)- treated A-2058 as responder cells; the other melanoma cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…A multistep model of invasion suggests that cancer cells must first adhere to the ECM, proteolytically degrade the matrix, and finally migrate through this barrier to distant sites. 2326 In this study, CTHRC1 expression in melanoma cells was demonstrated to enhance melanoma cell adhesion and survival and correlated with modification of actin organization and cell morphology variation. The data obtained during this study, combined with previous data demonstrating upregulation of CTHRC1 in various solid cancers, suggest that CTHRC1 may potentially facilitate metastasis by promoting the survival, relocation, and implantation of cancer cells at secondary sites as well as resistance to subsequent chemotherapy.…”
Section: Discussionmentioning
confidence: 62%
“…A multistep model of invasion suggests that cancer cells must first adhere to the ECM, proteolytically degrade the matrix, and finally migrate through this barrier to distant sites. 2326 In this study, CTHRC1 expression in melanoma cells was demonstrated to enhance melanoma cell adhesion and survival and correlated with modification of actin organization and cell morphology variation. The data obtained during this study, combined with previous data demonstrating upregulation of CTHRC1 in various solid cancers, suggest that CTHRC1 may potentially facilitate metastasis by promoting the survival, relocation, and implantation of cancer cells at secondary sites as well as resistance to subsequent chemotherapy.…”
Section: Discussionmentioning
confidence: 62%